Financial Inclusion in Somalia: A Demand and Supply Side Dynamics - Nur, Abdulkadir Mohamed; Samatar, Elmi Hassan (Journal of Cultural Analysis and Social Change, 2026)
Financial inclusion is critical to enhancing further economic growth and shrinking the poverty gap, especially in fragile economies similar to Somalia. Regardless, there remains a lack of empirical studies detailing the existing demand and supply factors of financial inclusion in Somalia. This study aims to explore the financial inclusion's key determinants on individual and institutional factors in Somalia. The study employed a cross-sectional research design with random sampling to improve representation and mitigate selection bias. The results indicate that the strongest positive predictors of financial inclusion include income level, trust in the financial service provider, usage, and financial literacy. Meanwhile, the number of bank branches relate positively but insignificantly, highlighting the increasing relevance of mobile and online financial services. The study emphasizes improving financial literacy and public confidence in financial institutions while shifting the focus in Somalia from antiquated banking models to new digital infrastructure.